Diurnal pattern of nitrous oxide emissions from soils under different vertical moisture distribution conditions - Xu,Junzeng (Instituto de Investigaciones Agropecuarias, INIA, 2016)
The diurnal pattern of nitrous oxide (N2O) emissions is essential in understanding how weather and soil conditions influence the daily mean estimate of N2O fluxes. Incubation experiments were conducted to investigate the effects of vertical soil moisture distribution patterns on diurnal variation of N2O emissions. Clear diurnal patterns of N2O emissions on both surface watering (SW) and subsurface watering (SUW) treatments (SUW12, SUW15, and SUW18) were detected from soil sample (I), silty clay, and soil sample (II), sandy loam, where peak N2O fluxes usually occurred between 12:00 and 18:00 h. Different vertical watering patterns resulted in changes in the daily range of N2O fluxes and peak time. Mean fluxes from the SUW12, SUW15, and SUW18 treatments were 37.4%, 32.7%, and 43.3% lower than those from SW treatments from soil sample I, and 32.0%, 40.3%, and 41.1% from soil sample II. Moisture distribution patterns under SUW soils could be effective to mitigate N2O emissions. The N2O emissions from soil sample I ranged from178.3 to 2741.0 μg N2O m-2 h-1, which was more than in soil sample II with 7.0 to 83.7 μg N2O m-2 h-1. The different soil texture and N content level might account for the differences in magnitude of N2O fluxes from soils. The optimal soil moisture condition for peak N2O fluxes in the SW treatment had relatively narrower ranges than the SUW treatments with 46% to 60% water-filled pore space (WFPS) for soil sample I and 26% to 34% WFPS for soil sample II even though surface soil moisture for peak N2O fluxes were somewhat different from the previously reported optimal soil moisture range of 45% to 75% WFPS.